Determinants and outcomes of preterm births at a tertiary hospital in Ghana - Adu-Bonsaffoh, K.; Gyamfi-Bannerman, C.; Oppong, S.A.; Seffah, J.D. (Placenta, 2019)
Introduction Preterm birth remains an important clinical challenge with significant short and long-term complications although its burden in the developing world is not adequately explored. This study determines the incidence, specific determinants and outcomes of preterm birth at a teaching hospital in Ghana. Methods Retrospective review of singleton births at Korle-Bu Teaching Hospital (KBTH) in Ghana between 1st January to 31st December, 2015. Results Preterm birth (PTB) occurred in 1478 (18.9%) out of 7801 single deliveries with etiological distribution of 879 (59.5%) spontaneous and 599 (40.5%) provider-initiated phenotypes. Gestational age categorization (WHO classification) of the preterm births included 68 (4.6%), 235 (15.9%) and 1175 (79.5%) below 28, between 28-31 and 32–36 weeks respectively. Adverse perinatal outcomes (low birth weight, perinatal deaths and poor Apgar scores) but not adverse maternal outcomes (cesarean and maternal deaths) were significantly higher in preterm compared to term births. Major factors associated with PTB include advanced maternal age (>35 years), poor antenatal care, hypertensive disorders and preterm premature rupture of membranes (PPROM) whiles obesity was protective. There were 156 stillbirths (105.6 per1000 births) comprising 93 macerated (62.9 per 1000 births) and 63 fresh stillbirths (42.6 per 1000 births), and perinatal mortality rate of 119.8 per 1000 births. Discussion Preterm birth is highly prevalent with significant adverse outcomes among singleton gestations at KBTH in Ghana, with disproportionately higher spontaneous etiology compared to provider-initiated phenotype. A paradigm shift in clinical management of preterm births/prematurity is urgently required with proactively dedicated multidisciplinary team and involvement of the global community.